Household Social Expenditure in Ghana: Examining the Ex-Post Effects and Vulnerability to Poverty - Nkrumah, R.K.; Annim, S.K.; Afful Jr., B. (MDPI, 2021)
We estimate the effect of household social expenditure on vulnerability to poverty using the four latest cross-sectional waves of Ghana Living Standard Survey (GLSS) from 1999 to 2017. Using a 3-Stage Least Square and Quantile Regression, our results show a widening consumption ex-post welfare gap between the poorest households and the non-poor households in a per-dollar social expenditure. Further, we estimate the probability of an ex-ante poverty using vulnerability to expected poverty. The results, however, indicate that regardless of poverty status, household vulnerability to poverty increased consistently between 1999 and 2017, and the very poor households showing the severest vulnerability. Hence, it is concluded that social expenditure increases the chances of a poor household falling into chronic poverty a non-poor household into transient poverty in the future.
Research Article
Keywords: social expenditure; welfare; vulnerability; household; poverty